Association of location and diameter of alveolar antral artery to crest of alveolar bone in dentate and partially edentulous patients - A cone-beam computed tomography study - Rajashri Abhay Kolte; Abhay Pandurang Kolte; Priyanka Sunil Rahate; Pranjali Vijaykumar Bawankar (Wolters Kluwer Medknow Publications, 2021)
Background: One of the most challenging anatomical conditions to manage during sinus augmentation using lateral window approach is the alveolar antral artery (AAA) when it is unusually wide in diameter and passes through the area of the osteotomy with a complete intraosseous course. The purpose of this study was to investigate the association of location and diameter of AAA to the crest of alveolar bone in dentate and partially edentulous patients using cone-beam computed tomography (CBCT). Materials and Methods: Totally 100 CBCT scans of patients (50 dentate and 50 edentulous) were selected and analyzed. The location and diameter of AAA in the lateral wall of the maxillary sinus were evaluated in association with alveolar bone height with respect to three posterior maxillary teeth: first premolar (P1), second premolar (P2), and first molar (M1). Results: The diameter of AAA in dentate patients was higher in M1 region (1.32 ± 0.34 mm) than P1 (0.91 ± 0.20 mm) and P2 (1.07 ± 0.24 mm) regions as compared to edentulous patients. It was found that the location of AAA for P1 in the dentate group (22.35 ± 4.17 mm) was significantly higher than that of the edentulous group (20.37 ± 2.48 mm). A negative relationship has been found between age and the distance between the AAA canal and crest of the alveolar ridge in both dentate (P = 0.001) and edentulous (P = 0.003). Conclusion: A significantly negative relationship existed between age, diameter, and location of AAA in both the dentate and edentulous groups.